The powers of the bodies of the Social Fund of Russia to control the validity of social security - O. S. Kurchenko (Правоприменение)
The subject of the study is the norms of Russian legislation providing for the rights and obligations of the bodies of the Social Fund of Russia (SFR) to control the validity of social security. The variety of legal acts that regulate social security relations with the participation of SFR bodies makes it difficult to form a holistic view of the system of powers of these bodies to control the validity of social payments and services provided by the SFR.The purpose of the study is to systematize knowledge about the powers of the SFR bodies to control the validity of social security, to assess the current legal regulation in this part for its integrity and sufficiency to ensure targeted spending of the SFR budget.Methodology. Formal legal and comparative legal methods were used to achieve this goal. The research is based on the analysis of the norms of legislation on social security, which enshrine the rights of the SFR bodies to verify information and documents necessary for the appointment and payment of social security, and the practice of its application.The main results. These rights, in fact, represent the powers of the SFR bodies. The author proposes a classification of the control powers of the SFR bodies in the field under consideration for various reasons. The shortcomings of the current legal regulation of the implementation of control powers by the SFR bodies have been identified.Conclusions. In order to create a holistic legal framework for controlling the validity of social security provided by the SFR bodies, it is proposed to consolidate the powers of control in a generalized form in the Law on the Social Fund of Russia with the possibility of specifying them in other normative legal acts. At the same time, legal regulation should determine the actual basis for the use of the verification powers and the procedure for their implementation. As one of the directions of further research, the author identifies the question of the relationship between the control powers of the SFR bodies and the obligations of the recipient citizen to inform the SFR body about the circumstances entailing the termination of the right to social benefits or a change in its size.